Comparative evaluation of different culture media for the isolation and identification of common urinary pathogens - Chaturvedi, Aarti; Garg, Ritu; Singh, Varsha A. (International Journal of Research in Medical Sciences, 2017)
Background: Urinary tracts infections (UTIs) are one of the most common infections encountered in hospital as well as community settings. There is continuous increase in incidence of this infection leading to more consumption of antimicrobial drugs. Urine cultures occupy most of the workload of routine microbiology laboratories in developing country like India. Accurate and rapid identification of pathogens is the primary responsibility of a clinical microbiology laboratory. Methods: Mid-stream urine and catheterized samples were collected. Cultures were plated on blood agar, MacConkey agar and cysteine lactose electrolyte deficient media and incubated overnight at 35°C-37°C in ambient air. Colonies on the MacConkey agar, CLED agar and blood agar were also identified. The final identification of the isolates was done using standard identification protocol. Antimicrobial susceptibility was performed by Kirby- Bauer disc diffusion test according to the CLSI guidelines. Results: Out of 500 urine samples processed, 211 samples showed significant growth, 24 samples showed polymicrobial growth and 265 samples were reported sterile. Out of these 211, 199 showed pure growth and 12 showed mixed growths. Out of 199 pure growths, 126 were gram negative bacilli, 56 were gram positive cocci and 17 were yeast. All the gram-negative bacilli grown on all the media but most of the gram-positive cocci and yeast were unable to grow on Mac-Conkey agar and blood agar but grew successfully on CLED agar. Conclusions: So, in resource constrain laboratories, CLED agar can be used as media of choice for isolation of common uropathogens because it is user friendly, cost effective and decreases work load of the laboratories.